"A Thousand Minute Circumstances": Frankenstein, Westworld and Feminist Revolution. Issue 3 (4th May 2021) - Lorenz, Matt
ABSTRACT: Westworld, the HBO series created and written by Jonathan Nolan and Lisa Joy, is an indirect adaptation of Frankenstein that centers on two heroines, Dolores (Evan Rachel Wood) and Maeve (Thandie Newton), android "hosts" who struggle and suffer at the hands of their corporate handlers and of the "guests" who pay to visit a world without consequences. As an innovative feminist extension of Shelley's Frankenstein, Westworld levels an implied critique against the patriarchal, self-aggrandizing attitudes of Victor Frankenstein and of modern science, which seek to probe and dominate when they should nurture and respect. As such, Westworld valorizes a filial sphere in which creators devote themselves to the emotional well-being of their creations, in which familial ties engender healthy, fully actualized individuals, and in which these individuals develop the emotional strength and circumspection necessary to seek positive social change.